The emotional and motivational costs of poorly delivered academic feedback - David Reed Akolgo; Al Robiullah; Gerardo Ramirez (Frontiers in Psychology, 2025)
IntroductionThis study uses psychological reactance theory and self-determination theory to explore whether disrespectful or disorganized feedback affects student motivation and classroom engagement.MethodsA sample of 148 undergraduates read one of four vignettes describing professor feedback that varied by tone (respectful or disrespectful) and clarity (low or high hassle). After reading the email, students completed measures assessing their emotional reactions, perceptions of the professor, and willingness to participate in class.ResultsStudents who received disrespectful messages reported stronger negative emotions, lower trust in the professor, and reduced willingness to participate. High-hassle feedback also lowered engagement, particularly when combined with a respectful tone. Interaction effects indicated that hassle weakened the positive impact of respectful communication.DiscussionStudents interpret tone and structure in feedback as signals of respect and fairness. When communication feels disrespectful or unnecessarily complicated, students may disengage or comply for the sake of appearances while withdrawing emotionally. These findings suggest that instructors can protect student motivation by using clear and respectful language, especially in digital formats where intent can be harder to interpret.